Effects of chronic cytochrome P-450 inhibition on the course of hypertension and end-organ damage in Ren-2 transgenic rats - Čertíková-Chábová, Věra; Kramer, Herbert J; Vaněčková, Ivana; Vernerová, Zdenka; Eis, Václav; Tesař, Vladimír; Škaroupková, Petra; Thumová, Monika; Schejbalová, Stanislava; Husková, Zuzana; Vaňourková, Zdeňka; Kolský, Alexander; et al. (Vascular pharmacology, 2007)
The aim of the present study was to evaluate the effects of inhibition of cytochrome P-450 (CYP) activity by 1-aminobenzotriazole (ABT) and by CoCl(2), first, on the development of hypertension when treatment was started in young male heterozygous Ren-2 transgenic rats (TGR) and, second, on blood pressure (BP) when treatment was started in adult TGR with established hypertension. Normotensive Hannover Sprague-Dawley (HanSD) rats served as controls. In addition, the renal cortical activities of omega-hydroxylase, the enzyme catalyzing the formation of 20-hydroxyeicosatetraenoic acid (20-HETE), and of epoxygenase, the enzyme responsible for epoxyeicosatrienoic acids (EETs) production, and urinary excretion of 20-HETE and EETs in TGR and HanSD rats were assessed. TGR have higher renal tissue omega-hydroxylase activity and urinary excretion of 20-HETE but have significantly lower renal epoxygenase activity and urinary excretion of EETs than HanSD rats. Treatment of young TGR with ABT and CoCl(2) attenuated the development of hypertension and cardiac hypertrophy and prevented glomerulosclerosis. Administration of ABT and CoCl(2) in adult TGR decreased BP, cardiac hypertrophy, but did not reduce glomerulosclerosis. Our data suggest that altered production and/or action of CYP-derived metabolites play a permissive role in the development and maintenance of hypertension in TGR by enhancing ANG II-induced vasoconstriction.
Keywords: financování organizované; Animals; heterozygot; Vasoconstriction; hypertenze; Hydroxyeicosatetraenoic Acids; kobalt; cytochrom P450 CYP4A; vazokonstrikce; Glomerulosclerosis, Focal Segmental; Kidney Cortex; Renin; triazoly; Enzyme Inhibitors; Heterozygote; Cardiomegaly; kyseliny hydroxyeikosatetraenové; Oxygenases; renin-angiotensin systém; Renin-Angiotensin System; oxygenasy; krevní tlak; inhibitory cytochromu P450; Rats, Sprague-Dawley; Financing, Organized; kůra ledviny; Hypertension; Triazoles; Male; modely nemocí na zvířatech; potkani Sprague-Dawley; inhibitory enzymů; systém (enzymů) cytochromů P-450; Disease Models, Animal; krysa rodu Rattus; kardiomegalie; Random Allocation; Cytochrome P-450 CYP4A; zvířata; mužské pohlaví; Blood Pressure; fokálně segmentální glomeruloskleróza; Cobalt; renin; Cytochrome P-450 Enzyme Inhibitors; Rats; Cytochrome P-450 Enzyme System; náhodné rozdělení